(untitled) (Experimental biology, 2015)
Biophysical properties of aurikulyarny bioactive points of skin of animals under influence a stress of factors of environment are investigated. The raised indicators of conductivity in all biologically active points of skin of animals under the influence of noise in comparison with norm are found. Change of indicators of biopotentials of bioactive points of skin of animals being under vibration concerning norm is proved. There is no special difference in biophysical indicators of biologically active points left and right ear sinks.